Remittance inflow and smallholder farming practices. The case of Moldova. (January 2018) - Piras, Simone; Vittuari, Matteo; Möllers, Judith; Herzfeld, Thomas
Abstract: In the Republic of Moldova, a large number of households that received land shares after the break-down of the collective farm structure currently focus on semi-subsistence agriculture. Often, one or more members of these households have migrated abroad. This paper aims at assessing the impact of remittances on their agricultural production practices and investments. The authors rely on the rotating panel dataset of the Household Budget Survey for the period 2007–2013, and on an original survey carried out on a sample of 126 households in 2015. To test if remittance recipients replace family labour and self-produced inputs with mechanisation services and purchased inputs, a shadow agricultural wage is estimated. Logistic regressions are used to assess whether the occurrence of investments (farmland, machinery, or dairy cattle) is more probable in the case of remittance inflow. The results show that recipient households reduce their drudgery by substituting family labour and self-produced seeds and feed with mechanisation services and purchased inputs, without necessarily increasing production efficiency. The relationship between remittances and agricultural investments is very weak or negative. However, qualitative insights demonstrate that many investments (greenhouses, rototillers, walnut orchards, etc.) were possible thanks to remittances. Although most recipients do not invest in agriculture, the minority that does invest has access to remittances.